Etika Kepemimpinan Islami Pangeran Diponegoro dalam Perspektif Babad Diponegoro dan Kontribusinya bagi Pengembangan Pendidikan Islam - Dwi Ramadhani; Naufal Alawy (Quantum Edukatif: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the spiritual, moral, and leadership values of Prince Diponegoro as portrayed in the Babad Diponegoro and explores their relevance to the development of Islamic education in Indonesia. Using a library research approach, the study analyzes the Babad Diponegoro manuscript as the primary source and employs historical literature and Islamic educational theories as secondary sources. Content analysis is used to identify key themes related to Diponegoro’s spirituality, moral critique, and ethical leadership, which are then connected to Islamic ethical frameworks proposed by Al-Ghazali, Ibn Miskawaih, and Syed Naquib al-Attas. The findings indicate that Diponegoro’s ascetic spirituality expressed through laku prihatin and the study of Islamic sciences served as the foundation of his character and struggle. His critique of moral decline in Javanese society underscores the importance of ethical education grounded in Islamic values and local cultural context. His leadership ethos, which emphasized trustworthiness, justice, empathy, and moral restraint in warfare, reflects prophetic leadership principles relevant to Islamic education. Moreover, Diponegoro’s spiritual resilience during exile demonstrates mental strength that is essential for character formation. This study concludes that the Babad Diponegoro is a rich source of Islamic educational values and can be integrated into Islamic Education curricula, particularly in the development of ethics, leadership, and spiritual character.